Efficacy and safety of percutaneous patent foramen ovale closure in patients with a hypercoagulable disorder. Issue 4 (16th June 2021) - Ben‐Assa, Eyal; Herrero‐Garibi, Jesús; Cruz‐Gonzalez, Ignacio; Elmariah, Sammy; Rengifo‐Moreno, Pablo; Al‐Bawardy, Rasha; Sakhuja, Rahul; Lima, Fabio V.; Demirjian, Zareh N.; Ning, Mingming; Buonanno, Ferdinando S.; Inglessis, Ignacio; et al.
Abstract: Background: Transcatheter closure of patent foramen ovale (PFO) in patients with cryptogenic stroke reduces the rate of recurrent events. Although presence of thrombophilia increases the risk for paradoxical emboli through a PFO, such patients were excluded from large randomized trials. Objectives: We compared the safety and efficacy of percutaneous PFO closure in patients with and without a hypercoagulable state. Methods: Data from 800 consecutive patients undergoing percutaneous PFO closure in our medical center were analyzed. All patients were independently evaluated by specialists in neurology, cardiology, hematology, and vascular medicine. A post‐procedural treatment of at least 3 months of anticoagulation was utilized in patients with thrombophilia. Follow‐up events included death, recurrent neurological events, and the need for reintervention for significant residual shunt. Results: A hypercoagulable state was found in 239 patients (29.9%). At median follow‐up of 41.9 months, there were no differences in the frequencies of stroke or transient ischemic attack between patients with or without thrombophilia (2.5% in non‐hypercoagulable group vs. 3.4% in hypercoagulable group, log‐rank test p = 0.35). There were no significant differences in baseline demographics, echocardiographic characteristics, procedural success, or complications between groups. Conclusion: Percutaneous PFO closure is a safe and effective therapeutic approach for patients with cryptogenic stroke and an underlying hypercoagulable state.